MusicBeetle: Intelligent music royalties collection and distribution system - Serrão, C.; Carvalho, H.; Carvalho, N (Proceedings of the 5th International Conference on Cloud Computing and Services Science, 2015)
Music industry has been completely disrupted by a range of new online digital services and social network- ing systems that has forever changed the way users and businesses experience and use music. This had a tremendous impact on the established music business models that had guided a dozen year-old industry. On what concerns business music users, i.e. businesses that make use of music as part of their own business model, and on the business relation they establish with author societies or their representatives, they are re- quired to pay royalties for the use of music. These royalties need to be distributed and authors will have the opportunity to see their work rewarded properly. The proper distribution of royalties is a non-transparent and complex process. In this paper, the authors present a system, called MusicBeetle that enables the identi- fication, collection and distribution of music royalties through the usage of decentralised system and low cost hardware devices.